مذهب الحافظ لبن كثير في التعامل مع الحديث المرسل من خلال تفسيره - عماري, أيوب (University Of Eloud جامعة الوادي, 2019)
"الملخص: تناولت هذا الموضوع ""مذهب الحافظ ابن كثير في التعامل مع الحديث المرسل من خلال تفسيره"" من خلال ثلاث جوانب: فأما الجانب الأول: فتطرقت فيه لعصر ابن كثير من الناحية السياسية والاجتماعية والثقافية والدينية، ثم ترجمةٌ مختصرة لابن كثير، بينتُ فيها جزء من حياته العلمية، ثم نبذة يسيرة عن تفسيره للقرآن العظيم. وأما الجانب الثاني:كان عن دراسة نظرية للموضوع، تطرقت لتعريف الحديث المرسل فيه،ومذاهب العلماء في الاحتجاج به. وأما الجانب الثالث:كان عبارة عن دراسة تطبيقية للموضوع على أحاديث مختارة تيسرت لي دراستها، مخرجة من مظانها، عليها كلام العلماء، إن وجد، ثم الحكم عليها، بينتُ من خلالها، منهج ابن كثير في ذكر الحديث المرسل، ومذهبه في الاحنجاج به، وختمت هذا الموضوع بنتائج وتوصيات، أهمها أن ابن كثير على مذهب المحدثين في الاحتجاج بالحديث المرسل. " " The summary: This topic has dealt with ""the doctrine of Al-Haafiz Ibn Katheer in dealing with the transmitted Hadeeth through its interpretation"" through three aspects: The first aspect: was related to the age of Ibn Katheer in terms of political, social, cultural and religious, then a brief translation of Ibn Katheer, in which he showed part of his scientific life, and then a brief overview of his interpretation of the Great Qur'an. Concerning the second aspect it was about the theoretical study of the subject, which dealt with the definition of the hadeeth in it, and the doctrines of the scholars in protesting it.The third aspect , it is about practicing a study about the topic which centers around a selected Hadeeth that was easy for me to extracted from its origins put on it the words of scholars if they are found decreed . Clarifing through it the doctrine of Ibn Katheer in dealing with the transmitted Hadeeth through interpretation and doctrine taken as a complaint . The topic was concluded , by some results and advises the most importance out of it is that Ibn Katheer is on the doctrine of the Hadeeth tellers complaining about the transmitted Hadeeth. "
مذكرة ماستر تخصص علوم الحديث
Keywords: الحافظ ابن كثير-الحديث المرسل- تفسيرالقرآن; Al-Hafiz Ibn Katheer-Hadith Al-Mursal - Interpretation of the Qur'an